Implementation of Interactive Learning in Linear Algebra Courses using HTML - Septiana Wijayanti; Nugroho Arif Sudibyo; Adri Surya Kusuma; Faizal Khusnul Ramatullah (Universitas Cokroaminoto Palopo, 2021)
Education or learning is essentially a process of optimizing a child's potential towards the achievement of certain abilities as a standard for learning outcomes, by the task of growth and development which is reflected in the selection of life skills. Generating motivation regarding the learning material will increase the interest of learners in participating in learning. Giving attention to learning can be through learning media. Learning media is very developed and continues to increase due to the use of computer information technology. The purpose of this project was to examine how HTML may be used to enable interactive learning in Linear Algebra courses. The experimental research method employed in this study was the One Group Pre-test Post-test Design. Data analysis in this study used the Wilcoxon test because the data were not normally distributed. The results indicate that student scores significantly improved between the pre-test and post-test. Interactive media affect online learning today, so it is hoped that teachers/lecturers will use interactive media more in learning.